EVALUATION OF INNOVATIVE TEACHING METHODS USING MODERN INFORMATION TECHNOLOGIES - Spaska, Anastasiya; Kozub, Halyna; Abylasynova, Gulaim; Kozub, Vladyslav; Koval, Yuliya (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
The aim of the study was to identify the effectiveness of innovative teaching methods using modern information technologies (IT) in four leading universities of Kyrgyzstan and Ukraine. The study was conducted on the basis of a SWOT analysis for each university. The selection of universities ensured comprehensive coverage of different types of educational institutions, from public to private. The data collected included a comparative analysis of the selected universities, as well as an assessment of the available digital platforms and technical support. The main results of the study were aimed at identifying the strengths, weaknesses, opportunities, and threats associated with the introduction of modern IT in the educational process. This allowed understanding which technologies and methods were most effective in improving the quality of education. A comparative analysis of universities helped identify general trends and specific challenges for each institution. In particular, Ukraine’s educational system is characterized by a developed network of higher education institutions, the implementation of the Bologna system, and the active use of IT in education. It is determined that the educational system in Kyrgyzstan is developing, in particular in terms of the introduction of modern technologies, both in public and private universities. The study formulates recommendations for improving the use of modern IT in teaching, in particular, for teacher training and attracting additional resources. The results of the study can be used for further development of the country’s educational system, with a focus on innovative approaches in selected universities in Kyrgyzstan and Ukraine.